A Mobile-Enabled Adaptive Gamification Framework for Programming Education - Alshalabi, Ibrahim Alkore; Alrawashdeh, Tawfiq; AbuKaraki, Anas; Alksasbeh, Malek Zakarya (International Journal of Interactive Mobile Technologies (iJIM), 2025)
While traditional teaching and learning methods in education have turned to be more active and engaging with the help of technology, this study proposes a Holistic Gamification Learning Adventure (HGLA) framework, which integrates gamification principles, multidimensional progression, and narrative-driven experiences for programming education. Different from most other gamification models, adaptive pathways and collaboration in the HGLA framework ensure novelty in accommodating diverse learning styles and proficiency levels of both novice and advanced programmers. It’s a framework that uses responsive design to ensure access across devices, creating ubiquitous learning environments. The embedment of gamified missions and narrative-driven challenges shall make students active participants instead of passive observers, while the motivation, engagement, and retention concerning programming concepts shall be developed. The multi-dimensional progression within the framework caters to individual learning paces, ensuring an individualized educational experience for deeper conceptual understanding and long-term retention. The present study shows how the HGLA framework has transformed programming education into an adaptive, inclusive, and impactful learning journey—a beacon of change in innovative teaching methodologies.